The Effects of Thoracic Foam Roller Exercise for on Thoracic Kyphosis Angle and Trunk AROM - Wang, Joongsan (Journal of International Academy of Physical Therapy Research, 2025)
Background: Foam roller exercise is widely used for myofascial release and improving joint range of motion. Objectives: This study aimed to identify the most effective session of thoracic foam roller exercise by examining changes in thoracic kyphosis angle (TKA) and trunk active range of motion (AROM) in healthy males in their 20s. Design: Single-group design. Methods: The study analyzed changes in TKA and trunk AROM across sessions following the application of a thoracic foam roller exercise for 45 seconds per session over three sessions in 16 healthy males in their 20s. Results: Compared to pre-test values, TKA significantly decreased and trunk AROM significantly increased after thoracic foam roller exercise (P<0.01). Post hoc analysis showed a significant decrease in TKA in session 3 compared to session 1 (P<0.01). Trunk AROM (flexion, left lateral flexion, right lateral flexion) showed significant changes in sessions 2 and 3 compared to session 1 (P<0.01). Right rotation significantly improved in session 3 compared to session 1 (P<0.01). Conclusions: For managing thoracic vertebral alignment in healthy males in their 20s, three sessions of thoracic foam roller exercise per day are recommended. For improving trunk AROM management, two sessions per day be sufficient.